Identifikasi Nilai Konstanta Bentuk Daun untuk Pengukuran Luas Daun Metode Panjang Kali Lebar pada Tanaman Hortikultura di Tanah Gambut - Djoko Eko Hadi Susilo (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The purpose of this research is to know and identification constanta value of leaf shape for leaf area measurement using length cross width of leaf of horticulture plant in peat soil. This research was conducted from February to May 2015 in Palangka Raya City, Central Kalimantan. This research implemented by observed of leaf from 32 species of horticulture plant in peat soil. In every species, was observed 30 leaf (lamina). Measuring leaf area absolutelly using on grid paper or millimeter graph paper, and than measuring ratio if leaf area is can finding using length cross width of leaf. Result of this research, showed that 32 species of horticulture plant in peat soil have regularity of leaf shape and can identified of constanta value for leaf area measurement using length cross width of leaf.Leaf area measurement using length cross width of leaf is alternative technique because easier (simple), quick (fast), low cost, and accurate to plant growth analysis for non-destructive methods. Leaf area measurement not explain plant growth only, but many purposes was can resulted from it. This research suggested to identification of constanta value of leaf shape for another species horticulture plant in peat soil cultivation.